Requirements identification using high level carotene text classification concept for distributed agile team communication - Zainal Abdin, Nor Hidayah (2019)
Communication plays an important role to deliver the correct information. It is one of the biggest issues frequently happened in distributed agile team environment especially in text messaging. Among the issues are exchanging information using unstructured communication platform, misunderstanding on the information communicated and lack of proper documentation. If they require references on the requirements, they need to scroll back to their communicated text messages to identify it. To solve these issues, we studied the High Level Carotene concept that does automatic cascade and cluster text classification. This concept relies on training dataset. For this study, we adopted the cascade and cluster classification concept but rely on the hash tag function. This technique is called as High Level Carotene (HLC) technique that embedded into the tool that can identify the requirements information by classifying the text messages. The cascade classification split the sentences into words and cluster classification grouped it into the same cluster. For the objectives of this study, we identify the text classification technique for requirements identification in text messages, design the solution and evaluate the technique. In this study, there are related issues and solution for agile team communication and brief description of the HLC technique design and implementation for messages text classification function in the Agile Communication Management (AgileCom) tool. Lastly, this study concluded by the HLC technique effectiveness and usability evaluation results